Pengaruh Air Cucian Beras terhadap Pertumbuhan Tinggi Batang Tanaman Terong (Solanum melongena L.) - Setiawan, Dony (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Eggplant (Solanum melongena L.) is a vegetable plant that is planted to use its fruit as food ingredients, such as fresh vegetables or processed into various types of dishes because of its delicious taste. This study aims to determine the effect of rice washing water on the growth of eggplant (Solanum melongena L.) plant stems. The design used in this study was a Completely Randomized Design (CRD), consisting of 3 treatments with 9 replications, namely: P1 (750 ml of rice washing water + 750 ml of plain water); P2 75% (1125 ml of rice washing water + 375 ml of plain water); and P3 100% (1500 rice water). The observed variable was the height of eggplant (Solanum melongena L.) stems. The results of this study indicate that there is an effect of giving rice washing water on the growth of eggplant (Solanum melongena L.) plant stems. The best result was in the 3rd treatment with 100% rice washing water, while the treatment using 50% plain water had the lowest result.